Plant dependency and risk management in the Andean Puna during the Mid to Late-Holocene. (December 2022) - Pintar, Elizabeth; Fernanda Rodríguez, María
The archeology of the Puna, a high elevation desert in South America, gives us a long-term perspective on the role of wild plants in people's diets during the Holocene. We explore the impact of aridification on the use of edible wild plants among desert people through the study of macrobotanical remains. Our goal is to examine the variation in plant dependency and risk management strategies used over time, in particular during the drought of the Middle Holocene (ca. 8700–4500 BP). The macrobotanical record suggests the use of risk-averse strategies in order to cope with unpredictable resource productivity. Hunter-gatherers relied on carbohydrate rich resources from the vega wetlands and tolar shrublands, such as roots and tubers, as well as low-ranked seeds, stems, leaves, and fruits. They also obtained non-local edible plants by strengthening ties and forming safety nets with groups living in different ecozones that were not subject to the same resource fluctuation. Social interaction with areas lying beyond the ecological boundaries of the Puna has a longstanding tradition in this area beginning in the Early Holocene, and was likely a means of providing food security to populations whose subsistence depended mainly on camelid hunting, and eventually camelid pastoralism. A notable increase in that interaction began during the Late-Holocene, which was a period of lesser aridity, with the introduction of corn and quinoa.